Leucoplasias homogêneas e não homogêneas: análise clínica e histopatológica - Gimenez, Lara Cristina Oliver [UNESP] (2011)
Leukoplakia is a lesion of the oral cavity which term refers only to the clinical aspect and because it is widely associated with smoking and have big importance because of its potential for malignancy, the diagnosis for a possible treatment with the removal of causative factors becomes paramount. This study aimed to observe the evolution of postoperative leukoplakia lesions diagnosed in the Semiology clinic of the University of Dentistry of Araçatuba (FOA) as well as its correlation with smoking and family history of cancer of the participants. The study was conducted through a retrospective analysis of 10 patients. The participants passed by a new appointment afer the initial examination and biopsy performed at least three years, to check cases of recurrence or neoplastic conversion. To facilitate a better understanding and management of this type of disease, we use the classification that divides the lesions leukoplakia lesions non-homogeneous and homogeneous. From the 8 patients with lesions homogeneous, five quit smoking even before the first consultation and they showed no recurrence of the injury, from the other three, two relapsed and continued smoking, and of these, one with a clinical suspicion of malignancy reported as hyperkeratosis with histopathology moderate dysplasia. And the other patient with homogeneous lesion in the first consultation quit smoking between the time between the first consult to the recent and showed recurrence of the lesion without malignancy. The other two patients attended at the first appointment had non-homogeneous lesions. One continued smoking and presented a recurrence of the lesion, and once performed a biopsy, it was found hyperkeratosis with moderate dysplasia. The other one, already features in treatment for squamous cell carcinoma, and this one, stopped smoking between...